Tropic thunder [videorecording (Blu-Ray)] - Stiller, Ben, 1965-; Stiller, Ben, 1965-; Stiller, Ben, 1965-; Stiller, Ben, 1965-; Black, Jack, 1969-; Downey, Robert, Jr., 1965-; Ruivivar, Anthony (Paramount, 2017)
While filming an action movie in the jungle, death and hilarity ensue as the lead actors believe the murderous heroin-producing gang they encounter is a part of the script.